«Lo Credo en romant»: una versione provenzale del Credo dal ms. Firenze, BML, Ashburnham 105. Edizione, traduzione, commento - Barillari, Sonia Maura (Vox Patrum, 2023)
The article proposes the edition of the transposition of the Creed in Provençal verse handed down from the manuscript ms. Firenze, BML, Ashburnham 105. The manuscript is a miscellany of texts in the Provençal language datable to the 14th century and exemplified for personal use by Peyre de Serras, an apothecary who lived in or near Avignon in the mid-14th century. Many of the works contained therein are of a hagiographic or devotional nature: among the latter, the Provençal versions of three ‘customary’ prayers – the Our Father, the Hail Mary and the Creed – are of particular interest, due to the tenacious resistance of the ecclesiastical hierarchies of the Romance-speaking countries to the possibility of allowing lay people to recite these prayers in their vernacular. The importance of this edition lies in the fact that in the current state of knowledge, the proposed text is the only version of the Creed in Provençal that has come down to us. Of equal interest are the relations it may have had with the Cathar heresy in a territory and at a chronological height – Provence in the first half of the 14th century – in which many forms of religiosity condemned as heretical were still deeply rooted in the hearts and consciences of many of the faithful.